Análise da aproximação tamm-dancoff + projeção em um modelo solúvel - Mizukami, Akiyoshi; Oliveira, Sérgio Augusto Carias de (Semina: Ciências Agrárias, 1980)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} @font-face {font-family:"Microsoft Sans Serif"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627421663 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The three sucessives aproximation Hartree-Fock + Tamm-Dancoff + Projection for many bodies tratament are applied to a model with exact solution developed Lipkin et al. Luck model is constitued of N fermions in two N-fold degenerated levels and interacting via monopole-monopole. The metod is tested by comparing its results with the exact solutions.